Intrinsic factor and vitamin B12 complex-loaded poly[lactic-co-(glycolic acid)] microspheres: preparation, characterization and drug release - OGAN, AYŞE; KAYAMAN APOHAN, NİLHAN; DEMİR, SERAP (WILEY, 2008)
BACKGROUND: Vitamin B12 is an essential vitamin required by all mammals. Absorption of vitamin B12 is facilitated by binding of intrinsic factor-vitamin B12 complex to specific receptors in the ileum. In humans a deficiency of this vitamin or a lack of intrinsic factor leads to pernicious anaemia. The major objective of the present study was to prepare intrinsic factor-vitamin B12 complex-loaded poly[lactic-co-(glycolic acid)] (PLGA)-based microparticles and to investigate their release kinetics. RESULTS: PLGA copolymer was synthesized by the ring-opening polymerization method and characterized using gel permeation chromatography, Fourier transform infrared spectroscopy and H-1 NMR. The glass transition temperature measurement showed a single T-g at 40 degrees C. The intrinsic factor-vitamin B12 complex-loaded PLGA microspheres were prepared by a water-in-oil-in-water double emulsion solvent extraction/evaporation technique. An environmental scanning electron microscopy investigation demonstrated that the PLGA particles had a mean particle diameter of 38 gm. Interestingly, different drug release patterns (bi- and triphasic ones) were observed for vitamin B12-loaded and intrinsic factor-vitamin B12 complex-loaded microspheres. In contrast to the rapid release of vitamin B12 by itself, in vitro release tests showed that intrinsic factor and vitamin B12 in the complex were released from PLGA microspheres in a sustained manner over 15 days. CONCLUSION: PLGA microspheres can be an effective carrier for the intrinsic factor-vitamin B12 complex. (C) 2007 Society of Chemical Industry.
Keywords: poly [lactic-co-(glycolic acid)] (PLGA); vitamin B12; intrinsic factor; microspheres; drug release; BIODEGRADABLE POLYMERIC MICROSPHERES; IN-VITRO; MORPHOLOGY; PROTEIN; PROFILES